Importance of Rare DPYD Genetic Polymorphisms for 5-Fluorouracil Therapy in the Japanese Population - Hishinuma, Eiji; Narita, Yoko; Obuchi, Kai; Ueda, Akiko; Saito, Sakae; Tadaka, Shu; Kinoshita, Kengo; Maekawa, Masamitsu; Mano, Nariyasu; Hirasawa, Noriyasu; Hiratsuka, Masahiro (Frontiers in Pharmacology, 2022)
Dihydropyrimidine dehydrogenase (DPD), encoded by the DPYD gene, is the rate-limiting enzyme in 5-fluorouracil (5-FU) degradation. In Caucasians, four DPYD risk variants are recognized to be responsible for interindividual variations in the development of 5-FU toxicity. However, these risk variants have not been identified in Asian populations. Recently, 41 DPYD allelic variants, including 15 novel single nucleotide variants, were identified in 3,554 Japanese individuals by analyzing their whole-genome sequences; however, the effects by these variants on DPD enzymatic activity remain unknown. In the present study, in vitro analysis was performed on 41 DPD allelic variants and three DPD risk variants to elucidate changes in enzymatic activity. Wild-type and 44 DPD-variant proteins were heterologously expressed in 293FT cells. DPD expression levels and dimerization of DPD were determined by immunoblotting after SDS-PAGE and blue native PAGE, respectively. The enzymatic activity of DPD was evaluated by quantification of dihydro-5-FU, a metabolite of 5-FU, using high-performance liquid chromatography-tandem mass spectrometry. Moreover, we used 3D simulation modeling to analyze the effect of amino acid substitutions on the conformation of DPD. Among the 41 DPD variants, seven exhibited drastically decreased intrinsic clearance (CLint) compared to wild-type. Moreover, R353C and G926V exhibited no enzymatic activity, and the band patterns observed in the immunoblots after blue native PAGE indicated that DPD dimerization is required for its enzymatic activity. Our data suggest that these variants may contribute to the significant inter-individual variability observed in the pharmacokinetics and pharmacodynamics of 5-FU. In our study, nine DPD variants exhibited drastically decreased or no enzymatic activity due to dimerization inhibition or conformational changes in each domain. Especially, the rare DPYD variant, although very low frequencies, may serve as an important pharmacogenomic marker associated with the severe 5-FU toxicity in Japanese population.